Genetic variants associated with disordered eating. Issue 6 (9th April 2013) - Wade, Tracey D.; Gordon, Scott; Medland, Sarah; Bulik, Cynthia M.; Heath, Andrew C.; Montgomery, Grant W.; Martin, Nicholas G.
<x xml:space="preserve">Abstract</x> Objective Although the genetic contribution to the development of anorexia nervosa (AN) has long been recognized, there has been little progress relative to other psychiatric disorders in identifying specific susceptibility genes. Here, we have carried out a genome‐wide association study on an unselected community sample of female twins surveyed for eating disorders. Method We conducted genome‐wide association analyses in 2, 564 female twins for four different phenotypes derived from self‐report data relating to lifetime presence of 15 types of disordered eating: AN spectrum, bulimia nervosa (BN) spectrum, purging via substances, and a binary measure of no disordered eating behaviors versus three or more. To complement the variant level results, we also conducted gene‐based association tests using VEGAS software. Results Although no variants reached genome‐wide significance at the level of p < 10−8, six regions were suggestive (p < 5 × 10−7). The current results implicate the following genes: CLEC5A, LOC136242, TSHZ1, and SYTL5 for the AN spectrum phenotype; NT5C1B for the BN spectrum phenotype; and ATP8A2 for the disordered eating behaviors phenotype. Discussion As with other medical and psychiatric phenotypes, much larger samples and meta‐analyses will ultimately be needed to identify genes and pathways contributing to predisposition to eating disorders. © 2013 by Wiley Periodicals, Inc. (Int J Eat Disord 2013; 46:594–608)